Islamic Bank Listed in Financial Market: Risk, Governance, Earning, and Capital - Budiman, Teguh; Kristanti, Farida Titik; Wardhana, Wardhana (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2017)
Islamic Bank is a bank that applies Islamic principles in running the business. Until 2015, there were 12 Islamic Bank in Indonesia; one of them already listed on the stock market. The purpose of this study was to analyze differences in the bank's soundness was assessed using a bank's risk profile, good corporate governance, income, and capital (RGEC) between listed Islamic Banks and the unlisted ones. Using the data period 2011-2015 used the independent t-test to test for differences. Statistical tests showed that there is no significant difference in credit risk as measured by NPF and Earning as measured by BOPO that represent cost efficiency between the two groups of companies. Listed Islamic banks have lower credit risk and greater efficiency than the unlisted onesDOI: 10.15408/aiq.v9i1.4011